1997
DOI: 10.1046/j.1365-2621.1997.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a thermal‐processed beverage prepared from roasted partially defatted peanuts

Abstract: SummaryThe effects of two thermal processing methods on physical and sensory properties of a 4 beverage prepared from finely ground, partially defatted roasted peanuts (Arachis hypogaea) were determined. Samples were either bottle-processed at 72 "C for 2 min or 111 "C for 8 min after homogenizing at 72 "C, or kettle-pasteurized for 2 min at 72, 77 or 82 "C before homogenizing at 72, 77 or 82 "C, respectively. Harsher thermal processing parameters increased the suspension stability and viscosity of bottle-proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…However, such formulations containing high amounts of both SPI and chocolate syrup resulted in higher viscosity and sweetness, thicker consistency, visibly darker color and less appealing appearance, ultimately lowering the consumer acceptability. This was in agreement with the observation that protein denaturation and aggregation, carrageenan interaction with water, hydrated polysaccharide–protein networks and hydrated lipid–protein complexes play important roles in controlling beverage characteristics (Hinds et al. 1997a,b,c).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, such formulations containing high amounts of both SPI and chocolate syrup resulted in higher viscosity and sweetness, thicker consistency, visibly darker color and less appealing appearance, ultimately lowering the consumer acceptability. This was in agreement with the observation that protein denaturation and aggregation, carrageenan interaction with water, hydrated polysaccharide–protein networks and hydrated lipid–protein complexes play important roles in controlling beverage characteristics (Hinds et al. 1997a,b,c).…”
Section: Resultssupporting
confidence: 91%
“…1987). Hinds et al. (1997a) observed that the visual stability in chocolate drink was lowest (0.11) compared with those of other commercial milk (1.00).…”
Section: Methodsmentioning
confidence: 99%
“…Final pilot‐plant scale protocol of the chocolate‐flavoured, peanut–soy beverage being developed in this study is given in Figs 1–3. Earlier work preformed in our laboratory on peanut beverage preparation (Hinds et al. , 1997a,b,c) guided the development process of chocolate‐flavoured, peanut–soy beverage.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity was measured using a Brookfield Viscometer (Model LVDV‐II+; Brookfield Engineering Laboratories, Inc., Stoughton, MA, USA) equipped with small sample adaptor (SSA 18/13R, 25 °C, 20 r.p.m.). VSI was measured by taking the ratio of the total height of the beverage to the height of the sediment collected after separation in a 250‐ml bottle (Hinds et al. 1997a,b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation